2018
DOI: 10.1111/all.13531
|View full text |Cite
|
Sign up to set email alerts
|

A marked shift in innate and adaptive immune response in chinese immigrants living in a western environment

Abstract: R E F E R E N C E S1. Safroneeva E, Straumann A, Coslovsky M, et al. Symptoms have modest accuracy in detecting endoscopic and histologic remission in adults with eosinophilic esophagitis. Gastroenterology. 2016;150:581-590. 2. Dellon ES. The pathogenesis of eosinophilic esophagitis: beyond the eosinophil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 9 publications
(10 reference statements)
1
16
0
Order By: Relevance
“…Chinese immigrants who had resided in Australia for more than 5 years demonstrated attenuated innate cytokine responses following TLR stimulation [38], increased genome methylation, and decreased gene expression compared to newly arrived immigrants [39]. Furthermore, the intensity of innate cytokine responses to TLR ligands and correlations between innate and adaptive antibody responses to pathogen-associated antibodies were significantly weaker in the long-term Chinese immigrants compared to newly arrived immigrants [40]. This supports the hypothesis that prolonged reduced exposure to microbial loads and biodiversity present in Westernized environments over time may attenuate key immunoregulatory mechanisms involved in modulating susceptibility to allergic disease.…”
Section: First-generation International Immigrantsmentioning
confidence: 99%
“…Chinese immigrants who had resided in Australia for more than 5 years demonstrated attenuated innate cytokine responses following TLR stimulation [38], increased genome methylation, and decreased gene expression compared to newly arrived immigrants [39]. Furthermore, the intensity of innate cytokine responses to TLR ligands and correlations between innate and adaptive antibody responses to pathogen-associated antibodies were significantly weaker in the long-term Chinese immigrants compared to newly arrived immigrants [40]. This supports the hypothesis that prolonged reduced exposure to microbial loads and biodiversity present in Westernized environments over time may attenuate key immunoregulatory mechanisms involved in modulating susceptibility to allergic disease.…”
Section: First-generation International Immigrantsmentioning
confidence: 99%
“…We initiated a study on asthma and allergy in Chinese immigrants in Australia in 2012 [8]. This current study is part of a large Chinese immigrant study and the recruiting method has been described elsewhere [14]. Twenty-two newly-arrived Chinese immigrants (living in Australia < 6 months) and 22 long-term adult Chinese immigrants (living in Australia > 5 years) were recruited with age and gender matched over 3 month period (Nov 2014 to Feb 2015).…”
Section: Study Participants and Designmentioning
confidence: 99%
“…We have found a marked shift in the innate and adaptive immune response between Chinese immigrants living in Australia for less than 6 months and more than 5 years. This was achieved by comparing the whole blood toll-like receptors (TLRs) pathway cytokine response and sera immunoglobulin G (IgG)-associated responsiveness to specific microbial/virus pathogens [14,15]. Recently, our team reported that Chinese immigrant children living in Australia show different microbiome diversity and composition compared to Chinese-born Chinese children [16].…”
Section: Introductionmentioning
confidence: 99%
“…Toll-like receptor signalling has inverted Ushaped response over time with the Western environment Jing Guo 1,2 , Yong Song 1,2 , Aarti Saiganesh 3 , Belinda Hales 3 , Anthony Bosco 3 , Peter Le Souëf 3,4 , Guicheng (Brad) Zhang (1,2). In the current study, we aimed to identify the dynamic changes of innate immunity in response to durations of exposure to Western environment relating to the increased risk of allergic development.…”
Section: Oc09mentioning
confidence: 99%